Konsep dan Implementasi Pendidikan Karakter di Sekolah Menengah Kejuruan (SMK) Berbasis Pondok Pesantren - Supriatna, Ece; Bahruddin, Ending; Hafidhuddin, Didin; Saefuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2014)
Vocational School (SMK; Sekolah Menengah Kejuruan) is an educational unit that aims to generate graduates all set to the workforce. Thus, the success of learning process in the School will affect the success in the future workforce. One of the problems facing on education field is the poor quality of the student’s character, since the character education is a major task on education at the same time is the mandate of the National Education System. SMK Plus Bina Teknologi Ibadurrahman YLPI Sukabumi (Engineering Vocational School Ibadurrahman YLPI Plus Sukabumi) is one of many schools that cares about the character education boarding-school-based. This study aims to determine the goals, curriculum, programs, methods and evaluation tools on character education and its implications for the students of Engineering Vocational School Ibadurrahman YLPI Plus Sukabumi. The study also aims to formulate the concept of character education boarding-school-based which can be implemented in the other Vocational School. The approach used is qualitative by using the students of Engineering Vocational School Ibadurrahman YLPI Plus Sukabumi as respondents. The main data collection techniques are questionnaires to students and observation and in-depth interviews with school administrators. The analysis technique is qualitative analysis which is the sensitivity of researcher becomes the most dominant element. The results of study in the field showed that the goal of character education in Engineering Vocational School Ibadurrahman YLPI Plus Sukabumi is to foster students to be virtuous human (Muttaqien) intelligent, noble and have the skills and interests for the benefit of mankind, by having ten characters. In addition, they are also required to achieve a goal that is both social and spiritual. The curriculum that is used, not only containing of the field of exacts, social, personality, and religion, but also integrated with the curriculum of boarding school. So that the program which organized by boarding school activities can be adjusted in line with the main goals of Vocational School system in general. The method used consists of a variety of methods with emphasis on methods of habituation. The evaluation tools used are in writing and not writing. At the side of the implications of the character education boarding-school-based is still weak, this shows by the evident from the number of students who have not yet established character which means they are lacking consistency. Based on these findings, the managers of the institutions should be aware of the decline in the character of their student. Therefore, it is recommended to organize a design of planning for character education in the future, since the vocational students will be in going to the workforce. On the other hand, the concept of character education should be emphasized to honesty, trust, self-awareness, love, affection, courteous, polite, patient, disciplined, independent, humble, and hard working.